Mechanisms of action of cytoplasmic microRNAs. Part 3. TNRC6-associated mechanism of miRNA-mediated mRNA degradation - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2022)
The scientific review presents the mechanisms of action of cytoplasmic miRNAs, namely posttranscriptional silencing: the TNRC6-associated mechanism of miRNA-mediated mRNA degradation. To write the article, information was searched using databases Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka. It is known that in the cytoplasm of cells in cases of short region, miRNA complementarities cause posttranscriptional silencing, using the first of the main molecular mechanisms: the TNRC6-associated mechanism of miRNA-mediated mRNA degradation. Mammalian AGO proteins have been shown to contain the conserved m7G-cap-binding protein motif (known as the MID domain), which is required to induce microRNA-mediated translation repression. After binding of this AGO motif to microRNAs, TNRC6 proteins (GW182) are recruited that, in turn, recruits various proteins (PABPC1, PAN3 and NOT1) involved in the induction of the target gene silencing. The authors state that tryptophan residues, which are placed in the hydrophobic pockets of TNRC6 protein partners, cause a high degree of affinity and specificity of interactions. Scientists believe that the TNRC6 protein when interacting with AGO proteins can simultaneously use three GW/WG repeats (motif 1, motif 2 and hook motif), which are located in the Argonaute-binding domain. Therefore, the TNRC6 protein can bind to three AGO molecules simultaneously. TNRC6 proteins are known to be PABP-interacting proteins whose interaction with PABP is mediated by conservative PABP-binding motif 2. TNRC6 proteins have been shown to interact with the cytoplasmic PABPC1 protein during mRNA translation and stabilization. It is shown that the CCR4-NOT protein complex is a highly conserved multifunctional multiprotein formation having 3'-5'-exoribonuclease activity, due to which it controls mRNA metabolism. Thus, the TNRC6-associated mechanism of miRNA-mediated mRNA degradation in the cytoplasm of the cell causes posttranscriptional silencing. In this mechanism, there is an interaction of TNRC6 with PABPC1 protein, recruitment of deadenylating complexes PAN2-PAN3 and CCR4-NOT by the TNRC6 proteins.